Self‐Assembly and Characterization of 3D Metallamacrocycles: A Study of Supramolecular Constitutional Isomers. Issue 14 (3rd April 2013) - Schultz, Anthony; Li, Xiaopeng; Moorefield, Charles N.; Wesdemiotis, Chrys; Newkome, George R.
Abstract: We report the self‐assembly and isolation of two metallamacromolecular constitutional isomeric pairs based on connectivity. Utilizing a robust dimer with varying substitution to the core benzene ring resulted not only in the isolation of the expected 60°‐oriented tetramer and 120°‐oriented hexamer but also in the unexpected isolation of a 60°‐oriented hexamer and a 120°‐oriented tetramer. These isomers were characterized by 1 H NMR spectroscopy and mass spectrometry (ESI‐travelling wave ion mobility), which revealed significant structural differences. Molecular modeling was utilized to aid in characterization. Abstract : Two metallamacromolecular constitutional isomeric pairs were self‐assembled based on connectivity. These isomers were characterized by 1 H NMR spectroscopy and mass spectrometry (ESI‐travelling wave ion mobility), which revealed significant structural differences. Molecular modeling was utilized to aid in characterization.